A novel mutation in exon 5 of the low density lipoprotein receptor gene in a Malay family with familial hypercholesterolaemia (FH) - Abdul Murad N. A.,; Hapizah M. N.,; Khalid Y.,; Khalid BAK,; Jamal R., (Pusat Perubatan Universiti Kebangsaan Malaysia, 2013)
Familial hypercholesterolaemia (FH) is an autosomal dominant inherited disease of lipid metabolism caused by mutations in the low density lipoprotein receptor (LDLR) gene. FH is clinically characterised by an elevated concentration of total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C), the presence of xanthomata and premature atherosclerosis. The objective of this study was to characterise the LDLR gene mutations in members of a family with FH. In total, 24 individuals were enrolled into this study. A proband from this family was diagnosed as FH based on the Simon Broome's criteria. Mutational screening was performed by polymerase chain reaction - denaturing gradient gel electrophoresis (PCR-DGGE) approach. Those bands that shifted on DGGE were subjected to DNA sequencing to confirm the mutation. We identified a base substitution, T to A at position 763 resulting in substitution of amino acid cysteine (C) to serine (S) at codon 234. This mutation was detected in exon 5 of the LDLR gene which involved the ligand binding domain and is designated as C234S mutation. This domain is important for the binding of LDLR to its ligand, apolipoprotein B100, in order to regulate the LDL catabolism through the LDLR mediated pathway. Mutation in this region may reduce the binding affinity of the LDLR to apolipoprotein B100. To our knowledge, this is a novel mutation worldwide. This mutation could possibly has important clinical implications in view of the high incidence of coronary artery disease (CAD) and sudden cardiac death (SCD) in the family.